Karawitan Composition of Sayong Senja | Komposisi Karawitan Sayong Senja - Pande Kadek Artha Mertha; I Ketut Muryana (GHURNITA: Jurnal Seni Karawitan, 2023)
The karawitan composition entitled Sayong Senja is a new composition, inspired by a natural phenomenon in the Kintamani area. Kintamani is indeed very famous for the cold air it produces which is often called Sayong Kintamani. The cold Kintamani air creates a cool atmosphere, giving rise to fertile agriculture, especially in citrus plantations. This made the stylists interested in bringing this into the Karawitan Composition. It seems that the reflection of the afternoon sun on the clouds gives rise to an interesting orange color in the cold of Kintamani in the afternoon. When the sunset says, the cold air of Kintamani can be overcome by the beauty of the sanyong. With the sunset sayingong which is supported by beautiful scenery and plantations, it can attract the attention of tourists and can also calm the heart of the air and atmosphere which is very supportive. The beauty of Sayong Kintamani in the afternoon is the main source in the process of making this composition. This work of art was created using the media of several instruments from Barungan Samara Pagulingan in the form of percussion creations with 15 supporters and a duration of 10 minutes. The reason for the stylist using the barungan is because, in samara pagulingan there are many patet and it has a sweet voice. In this composition, Sayong Senja uses the method of creating five sthiti ngawi sani.